Iceland’s involvement in global affairs since the mid-1990s. What features determine the size of a state - Baldur Þórhallsson 1968- (2006)
Fræðigrein The aim of this article is to examine Iceland’s international activity during the last decade. The case of Iceland will be placed in a ‘new’ conceptual framework intended to explain how the size of states may shape their international approaches. The conceptual framework includes six criteria that affect the notion of the size of states and influence their international behaviour; their internal and external ‘action capacity’ and ‘vulnerability’ in terms of these criteria define the size of states and may account for their international approaches. This case study tests Iceland’s increased international involvement within the framework in order to explain why Iceland has changed its international approach and become a more active player in the international arena since the mid-1990s. The country’s increased activity in the international system is explained by two interrelated features presented in the framework: a change of perception and preference by a large part of the Icelandic political elite and external pressure reflecting the view of international actors. This has led to a policy change at the domestic level. There has been a move away from an international approach built on historical bilateral relations, with a narrow focus on the concrete economic advantages to be gained from all overseas activity, to an approach based on more broadly defined interests and increased international activity within multilateral international organizations.